The influence of stick stiffness on the performance of ice hockey slap shots - Pearsall, D. J.; Montgomery, D. L.; Rothsching, N.; Turcotte, R. A. (Sports Engineering, 1999)
The purpose of this study was to examine the effects of shaft stiffness on puck velocity and response characteristics of carbon fibre composite ice hockey sticks during a slap shot. For this reason six elite male ice hockey players performed six slap shots with four sticks of different shaft stiffness. Results indicated: (1) the stick with lowest shaft stiffness of 13 KN m-1 produced the highest puck velocity, the greatest amount of shaft deflection, the longest time to peak deflection and the lowest peak Z forces; (2) the times to obtain peak forces in the Y and Z directions were similar across the levels of shaft stiffness; (3) puck velocity was influenced by the interaction of subject and stiffness and (4) variability in performance measures across subjects was greater than the variability across stiffness. Future studies are needed to address the effects stick construction has on different shots and stick handling skills, as well as to investigate the specific influence that skill and strength of the player has on the stick`s response.